Non-persistence with multiple secondary prevention medications for peripheral arterial disease among older hypertensive patients - Wawruch, Martin; Petrova, Miriam; Celovska, Denisa; Alfian, Sofa D; Tesar, Tomas; Murin, Jan; Trnka, Michal; Paduch, Tomas; Aarnio, Emma (Frontiers in pharmacology, 2024)
INTRODUCTION: The benefit of secondary prevention in hypertensive patients with peripheral arterial disease (PAD) is based on continual simultaneous taking of statins, antiplatelet agents and antihypertensive agents, preferably angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs). Our study was aimed at a) the analysis of the extent of non-persistence with multiple medication classes, and b) identifying factors associated with the likelihood of non-persistence. METHODS: In our cohort study, 3,401 hypertensive patients (1,853 females and 1,548 males) aged ≥65 years treated simultaneously with statins, antiplatelet agents and ACEIs/ARBs and in whom PAD was newly diagnosed during 2012 were analysed. A patient was classified as non-persistent when he/she was non-persistent with at least one of the three analysed medication classes. The most important characteristics associated with the probability of non-persistence were identified using the Cox regression. RESULTS: At the end of the follow-up period (mean length 1.8 years), 1,869 (55.0%) patients (including 1,090 females and 779 males) were classified as non-persistent. In the whole study cohort, factors associated with non-persistence were female sex, atrial fibrillation, and being a new user of at least one of the analysed medication classes; in males, they were university education, atrial fibrillation, and epilepsy, and, in females, being a new user. CONCLUSION: Identification of sex differences in factors associated with non-persistence makes it possible to determine the groups of patients in whom special attention should be paid to improving their persistence with a combination of medicines in order to ensure successful secondary prevention of PAD.